Early expression of the type III secretion system of Parachlamydia acanthamoebae during a replicative cycle within its natural host cell Acanthamoeba castellanii. Issue 3 (23rd August 2013) - Croxatto, Antony; Murset, Valérie; Chassot, Bérénice; Greub, Gilbert
Abstract The type three secretion system (T3SS) operons of Chlamydiales bacteria are distributed in different clusters along their chromosomes and are conserved at both the level of sequence and genetic organization. A complete characterization of the temporal expression of multiple T3SS components at the transcriptional and protein levels has been performed in Parachlamydia acanthamoebae, replicating in its natural host cell Acanthamoeba castellanii. The T3SS components were classified in four different temporal clusters depending on their pattern of expression during the early, mid‐ and late phases of the infectious cycle. The putative T3SS transcription units predicted in Parachlamydia are similar to those described in Chlamydia trachomatis, suggesting that T3SS units of transcriptional expression are highly conserved among Chlamydiales bacteria. The maximal expression and activation of the T3SS of Parachlamydia occurred during the early to mid‐phase of the infectious cycle corresponding to a critical phase during which the intracellular bacterium has (1) to evade and/or block the lytic pathway of the amoeba, (2) to differentiate from elementary bodies (EBs) to reticulate bodies (RBs), and (3) to modulate the maturation of its vacuole to create a replicative niche able to sustain efficient bacterial growth.